Adoption of Biologically Effective Dose of the Non-Target Lung Volume to Predict Symptomatic Radiation Pneumonitis After Stereotactic Body Radiation Therapy With Variable Fractionations for Lung Cancer - Jiao, Yuxin; Ren, Yanping; Ge, Weiqiang; Zhang, Libo; Zheng, Xiangpeng (Frontiers in Oncology, 2020)
Background: To establish lung biologically effective dose (BED)-based uniform dosimetric constraints for minimizing the risk of symptomatic radiation pneumonitis (SRP) from stereotactic body radiation therapy (SBRT) using variable fractionations in patients with lung tumors. Materials and methods: A total of 102 patients with primary or oligometastatic lung tumors treated with SBRT in our institution were enrolled into this study. The associations between the clinical and dosimetric parameters and the incidences of SRP were analyzed using univariate and multivariate Cox regression hazard models. The receiver operating characteristic curve (ROC) was generated to evaluate the predictive performance of lung-BED on the SRP risk compared to the physical dose. Results: SRP occurred in 11 patients (10.8%). In univariate analysis, the mean lung dose (MLD, p=0.002), V5 (p=0.005), V20 (p<0.001), and the percentage of non-target normal lung volume receiving more than a BED of 5–170 Gy (VBED5-170, p<0.05) were associated with SRP. Multivariate logistic regression analysis showed there existed a significant statistical correlation between SRP and VBED70 (p<0.001), which performed better than V5 or V20 on the ROC curves, resulting in an optimal cut-off value of lung-VBED70 of 2.22%. Conclusions: This retrospective study indicated that non-target lung-BED may better predict SRP from SBRT-treated lung cancer patients. To limit the lung-VBED70 below 2.22% may be favorable to reduce the incidence of SRP, which warranted further prospective validation.